A new anisotropic thermal conductivity equation for h-BN/polymer composites using finite element analysis. (October 2020) - Sun, Yingying; Zhou, Luyao; Han, Yu; Cui, Liu; Chen, Lin
Highlights: A new anisotropic κ equation for h-BN/polymer composites is successfully obtained. Heat transfer in h-BN/polymer composites is simulated by finite element method. Influence of h-BN and polymer on κ of composites is mathematically analyzed. Improving principle of directional thermal conductivity of composites is pointed out. Abstract: A new anisotropic thermal conductivity equation of h-BN/polymer composites was successfully derived from a series of numerical calculation and mathematical analysis. A simple finite element model of polymer composite filled with oriented hexagonal boron nitride (h-BN) was firstly established to simulate its thermal transportation. This numerical model was validated by other thermal conductive models and experimental data. Then the influence of many factors on the anisotropic thermal conductivity of h-BN/polymer composites was mathematically investigated, including matrix thermal conductivity, h-BN thermal conductivity, size, aspect ratio and oriented angles, interfacial thermal resistance, and non-uniform factors. It is found that thermal conductivity of polymer composites increases with filler content as a power function; decreases with interfacial thermal resistance in a negative power function form; increases almost proportionally with thermal conductivity of polymer matrix; does not change with h-BN thermal conductivity when the in-plane thermal conductivity of h-BN is higher than 100 W·m −1 ·K −1 and out-of-plane thermal conductivity of h-BN is higher than 2 W·m −1 ·K −1 ; and does not change with h-BN size under the same aspect ratio. With the increasing h-BN aspect ratio, in-plane thermal conductivity of composites increases, while out-of-plane thermal conductivity decreases. The change ranges of position and tilt angle correction factors were also obtained.